ANALISIS TERHADAP PERLINDUNGAN INVESTOR ASING DALAM KEGIATAN PENANAMAN MODAL DI SUMATERA UTARA (STUDI PUTUSAN MA-RI NO. 382 K/TUN/2010) - WAHANA GRAHAWAN MANURUNG (Universitas Sumatera Utara, 2013)
The role of law in supporting foreign investment is urgently needed in order to create legal certainty. In order to invite investors, especially foreign investors, to Indonesia, a consistent and integrated government regulation is needed in order to give the benefit not only to foreign investors but also to the Indonesian government, especially in increasing the economic growth which develop stable each year. The problems which were discussed in the research were about the government’s main policy on domestic and foreign investors based on Law No. 25/2007 on Capital Investment, the government’s attempt to give legal protection to foreign investors, and legal certainty for foreign investors in investing their capital in North Sumatera as it is stipulated in the Ruling of MA-RI no. 382 K/TUN/2010. The government should give equal treatment (not discriminative) to investors based on Law No. 25/2007 on Capital Investment. This equal treatment should be based on the principle of national treatment and the principle of the most favored nations. The protection given by the government to foreign investors is by improving the structure of legal provisions on investment and the implementation of these legal provisions, improving the facilities and services for investors, giving investment security, and controlling capital investment. The research of the case which occurs in the Ruling of the Supreme Court of the Republic of Indonesia No. 382/ K/TUN/2010 indicates that there is the law enforcement in the case which occurs in PT Socfin Indonesia (Socfindo) because there is no legal certainty. The overlapping of regulations can be seen in the publication of The Directives of the Governor of North Sumatera in 1971 and in 1972 although the land had legal basis owned by NV Sukaradja Cultuur My in the Land Certificate on January 28, 1928 and has been used as plantation area since 1928. The overlapping regulations can harm investors; in this case, PT Socfin Indonesia (Socfindo). Keywords: Protection for Foreign Investors